Teaching English to Children Orally and Aurally - Vicente Araujo; Aida Bastidas (Asociación Colombiana de Profesores de Ingles, 2016)
The relationship between a learner's age and his or her potential for success in second language acquisition is still the subject of much debate. Some authors argue that adults are able to learn a second language more rapidly than children, at least during the early stages of acquisition; other researchers hold that it is not necessarily true that adult learners cannot achieve a native-like accent in a second language.